Enhancing Community Knowledge Capacity in Waste Management Through a Waste Bank in Siwal Village, Sukoharjo - Alif Noor, Anna; Jumadi; Astuti, Dwi; Darnoto, Sri; Novita Sari, Dewi; Rudiyanto (Universitas Muhammadiyah Surakarta, 2025)
The increase in the volume and variety of waste in Siwal Village, Baki, Sukoharjo, has prompted the need for a management strategy that is not only technically oriented but also focuses on improving the knowledge capacity of the community. The growing population and settlements have led to waste that has not been managed optimally, with much of it still scattered on roads and public areas. This initiative aims to enhance community understanding and engagement in waste management through system digitalisation and continuous education. The partner in this initiative is BUMDes Citra Abadi Siwal, which currently lacks a structured waste management system and faces limitations in terms of human resources and infrastructure. Through outreach, training, and mentoring, the community is actively involved in developing community-based waste management systems. The education provided includes waste sorting, the use of a web-based waste bank system, and the importance of waste management as an economic opportunity. The results of the activity show an increase in community knowledge and participation, particularly in terms of waste disposal and sorting. The implementation of a digital system also facilitates record-keeping, monitoring, and enhances transparency in management. Despite challenges such as old habits and infrastructure limitations, this initiative has positively impacted environmental cleanliness and economic contributions through the BUMDes business unit. Thus, this initiative serves as a strategic step in enhancing community capacity toward sustainable waste management.